(untitled) (Research, Society and Development, 2021)
The objective of this study was to diagnose, the perspectives and reality of students graduating from the integrated technical course in agriculture at the Federal Institute of Education, Science and Technology of Minas Gerais - Campus Bambuí. The research was carried out through the application of a questionnaire submitted by e-mail and whatsapp, with authorization from the department responsible for the academic record, in addition to prior communication with the students themselves, to ensure greater adherence by them. The period studied covered the years from 1991 to 2019. The data analysis was based on 278 responses and were expressed as a percentage, to facilitate the understanding of the information. Through the profiles found, measures can be taken to improve the teaching and learning methodologies of the course and, consequently, reduce school dropout through, for example, greater interdisciplinarity, as well as finding alternatives that better prepare the student for an increasingly competitive agriculture, with the suggestion of offering greater contact within the institution with the latest technologies applied in the area.